Ancient Southeast Asia - Miksic, John N.; Goh, Geok Yian (Routledge world archaeology, 2017)
"Provides readers with a much needed synthesis of the latest discoveries and research in the archaeology of region, presenting the evolution of complex societies in Southeast Asia from the protohistoric period, beginning around 500 BC, to the arrival of British and Dutch colonists in 1600. Well-illustrated throughout, this comprehensive account explores the factors which established Southeast Asia as a region of unique cultural fusion. Miksic and Goh explore how the local population exploited the abundant resources available, developing maritime transport routes which resulted in economic and cultural wealth, including some of the most elaborate art styles and monumental complexes ever constructed"